Existing and emerging smoking cessation options for people with schizophrenia spectrum disorders. Issue 3 (2nd October 2018) - Caponnetto, Pasquale; DiPiazza, Jennifer; Signorelli, Maria; Maglia, Marilena; Polosa, Riccardo
Abstract: Tobacco cigarette addiction is a deeply entrenched behavior among people with Schizophrenia Spectrum Disorders, and consequently these individuals die an average of 25 years earlier than the general population. The aim of this review was to evaluate the state-of-the-science focused on cessation and reduction interventions for people with SSD. We searched peer-reviewed articles from medline, psycinfo, web of science, scopus, and cochrane library, about cessation interventions for people with SSD. The search was carried out by combining an exhaustive list of terms denoting schizophrenic disorder and smoking cessation treatment. The review search period was limited from January 2000–November 2018, 260 studies were identified and a total of 24 of studies were included in the final review. This review demonstrates the vulnerability of smokers with SSD and underscores the need for research in these areas with large enough sample sizes to detect treatment effects: 1) outcomes using and comparing standard treatments 2) long-term cessation/reduction outcomes 3) flexible treatment options 4) more research to develop the evidence-base for e-cigarettes intervention.